Transmission of HBsAg from mother to infant in four ethnic groups. Issue 6118 (15th April 1978) - Derso, A; Boxall, E H; Tarlow, M J; Flewett, T H
Abstract : Antenatal screening in the West Midlands during a three-year period identified 297 mothers who were chronic carriers of hepatitis B surface antigen (HBsAg)--a prevalence of about 1 in 850. About half of their infants had HBsAg in the cord blood, but of 122 infants followed up for over three months (mean 8.5 months) only 17 (14%) were still positive for HBsAg. Cord-blood HBsAg-positivity was evenly distributed among different ethnic groups, but the transmission rate was highest among the Chinese, and no carriers were discovered among 39 European infants. Raised serum transaminase concentrations were found in some of the carrier infants who were otherwise healthy. The results suggest that adequate follow-up of HBsAg-positive infants may be achieved by tests at 4 months and 1 year of age, and that the role of breast-feeding in mother-to-infant transmission of HBsAg is unimportant. The Chinese community may be a suitable population in which to test the effectiveness of specific immunoglobulin administration at birth in preventing the development of the HBsAg carrier state.